Pendekatan Sistematis Sudut Pintar dalam Upaya Meningkatkan Literasi di MI Cokroaminoto Sarwodadi - Huda , Alal; Wibawa, Raden Muhammad Rafiansyah Satria; Rishillia, Revieta Melati; Mistiar, Pipin Adi; Sihono , Annisa Nadhifah Putri; Azizi, Azkia Nurul; Anggara, Aditya Putra Tri; Syakira, Izza Kahla; Putri, Zahra Camelia; Afian, Izul Akbar Nur; Permana, Iman (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Education is a process of cultural change and noble personality values that are systematic and programmatic. Meanwhile, reading is a language skill and an important factor in the learning process, because by reading students can get information. Literacy is inseparable from the world of education and Knocking is a means for students to know, understand, and apply the knowledge they get in school. Children's lack of interest in critical thinking through reading is one of the common problems that occur in the world of education, including at MI Cokroaminoto Sarwodadi. To overcome this, it is necessary to optimize literacy programs through the development of structured programs, increasing the availability of reading materials, and strengthening literacy culture in the madrasah environment because this will be very crucial as a fundamental step in building a literate generation. The method used is Action Research with the first stage to see the basic problem, namely planning by conducting observations and interviews at MI Cokroaminoto Sarwodadi to collect data related to the condition of literacy in the madrasah. The results of the program implementasi were seen from the pretest numbers at the beginning of the meeting of MI Cokroaminoto Sarwodadi students who had low scores on the love of reading and did not have a love for reading books and a lack of understanding in critical thinking. By teaching and practicing with modules made by KKN 156 and packed with fun play, MI Cokroaminoto Sarwodadi students create a love for the world of literacy